Endometriosis may be associated with mitochondrial dysfunction in cumulus cells from subjects undergoing in vitro fertilization-intracytoplasmic sperm injection, as reflected by decreased adenosine triphosphate production - Hsu, Albert L.; Townsend, Paige M.; Oehninger, Sergio; Castora, Frank J. (Fertility and sterility, 2015)
To determine whether endometriosis is associated with mitochondrial dysfunction in cumulus (granulosa [GC]) cells of subjects undergoing IVF-intracytoplasmic sperm injection (ICSI). Prospective cohort study. An IVF clinic in a tertiary academic care center. Eleven women with endometriosis and 39 controls. None. Cumulus cell adenosine triphosphate (ATP) levels, mitochondrial DNA (mtDNA), and genomic DNA (gDNA) number. Cumulus cell ATP content was 65% lower in subjects with surgically proven endometriosis (median 312.5 attomoles/ng total DNA, interquartile range = 116.0–667.8) compared with controls (median 892.4 attomoles/ng total DNA, interquartile range = 403.0–1,412.2). There was no significant difference in mtDNA:gDNA ratio. There were no significant differences in age, body mass index (BMI), basal serum FSH level, total oocyte number, metaphase II (M2) oocyte number, metaphase I oocyte number, percentage of M2 oocytes, fertilization rate, implantation rate, or pregnancy rate (PR). Multivariate regression analysis showed significant positive correlations between ATP and [1] M2 oocyte number (r = 0.307) and [2] pregnancy (r = 0.332). There were also trends toward positive correlations between ATP and [3] age (r = 0.283), [4] total number of oocytes (r = 0.271), [5] percentage of M2 oocytes (r = 0.249), and [6] implantation rate (r = 0.293). There were no statistically significant correlations between mtDNA:gDNA ratio and any demographic factors or clinical outcomes measured. Surgically confirmed endometriosis may be associated with cumulus cell mitochondrial dysfunction in subjects undergoing IVF-ICSI for infertility, as reflected by decreased ATP production.